Formgiving: factoring elderly sitting furniture design through designers activity / Alya Mohd Azlan, Verly Veto Vermol, Rusmadiah Anwar and - Mohd Azlan, Alya; Vermol, Verly Veto; Anwar, Rusmadiah; Zainal Abidin, Shahriman (Universiti Teknologi MARA, 2021)
This work-in-progress paper in the research category presents a single case study taken through triangulated sample group which conducted in an advance to postgraduate coursework design data collection as in part of design innovation; which in this case overviewing chair design for the elderly. The study investigates the activity pattern of coursework master students, academicians and industrial designers’ level and patterns in reasoning that applies to the physic-chemical form and geometrical form that spanning further through functions, needs and values in product design embodiment. We examine whether triangulated group sampling contributes to the dominant feature of product development throughout Designers Design Sketch Information (DSDI) analysis that involves concurrent and retrospective think loud feedback. Through research being conducted within models and methods structured; contribute to multi-level direction that provides limitation understanding, design direction and experience drawback in product development.